A multiplexed hybrid LC–MS/MS pharmacokinetic assay to measure two co-administered monoclonal antibodies in a clinical study. (July 2014) - Xu, Keyang; Liu, Luna; Maia, Mauricio; Li, Jenny; Lowe, John; Song, An; Kaur, Surinder
Background: Combination therapies with monoclonal antibodies (mAbs) enhance therapeutic activity and may circumvent drug resistance. However, these studies present bioanalytical challenges for ligand-binding assays (LBAs). Recent MS-based protein quantification offers an alternative for bioanalysis.Results: A hybrid LC–MS/MS assay was developed to simultaneously measure human serum concentrations of two mAbs. Anti-idiotypic reagents that did not work in LBAs were successfully used for mAb affinity capture enrichment. Stable isotope-labeled peptide internal standards were employed. The mAb quantification involved measuring a signature CDR peptide derived from each mAb as a surrogate. Selected clinical samples were successfully analyzed.Conclusion: The multiplexed LC–MS/MS method provided a powerful quantitative tool for clinical PK assessment of co-administered mAbs without the requirement for stringent affinity capture reagents.